PENGARUH NILAI PERUSAHAAN, RISIKO BISNIS DAN TINGKAT PERTUMBUHAN TERHADAP IMBAL HASIL SAHAM (Studi pada Perusahaan yang Terdaftar di Jakarta Islamic Index Periode 2008-2011) - Ary Yunanto; Indratmo Yudono; Yulis Maulida Berniz (Universitas Peradaban, 2014)
In order to minimize investment losses that may be encountered when investing in stocks it needs to determine the factors that influence stock returns. This study investigates the influence of firm value, business risk, and growth rate on stock returns. The study employs book to market ratio, firm size, and sales price ratio as proxies for firm value, business risk, and growth rate. The results show that book to market ratio has positive impact on stock returns while sales price ratio has negative impact on stock returns. Furthermore, the results show that firm size has no significant impact on stock returns.